On teaching verb constructions with prepositions k and y at Lithuanian schools - Daunienė, Z. (Psichologija, 1963)
The article analyses Russian verb constructions with prepositions к and у and their equivalents in the Lithuanian language. Such verb constructions often constitute difficulties to Lithuanians learning the Russian language.Not knowing the exact meaning and usage of Russian prepositions, Lithuanian users often tend to replace Russian verb constructions with preposition к and by relevant constructions in their mother tongue, thus making rather many syntactic mistakes.The article analyzes the Russian verb constructions with prepositions к and у, expressing a variety of semantic relations and their parallel equivalents in Lithuanian are provided. Lithuanian constructions of such type can have either prepositional or non-prepositional form; on the other hand, the Russian preposition к has even several equivalents in the Lithuanian language (prie, pas, į), and the preposition y is also translated to Lithuanian in several ways (prie, pas, iš, etc.).The article simultaneously reviews two parallels of these constructions in the Lithuanian and Russian languages, namely: Russian verb constructions with prepositions к and у and Lithuanian constructions with prepositions prie and pas, expressing spatial and object-spatial relations.At the end, the article presents various exercises concerning verb agreement in the Russian and Lithuanian languages so that the learners can practice the correct usage of the mentioned verb constructions in Russian.
Keywords: teaching of the Russian language; usage of propositions